Concepts and models of management succession in family enterprises - Popczyk, Wojciech (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
One of the most important key factors for the development and growth of family businesses is the planning and implementation of management succession. This demanding and complicated process in the vast majority of cases ends in failure and loss of an intangible resource in the form of internal and external social capital, the carrier of which is the ownership family and which is the source of competitive advantage in the 21st century. The purpose of the article is to identify scientific concepts that will help understand the reasons for succession failures in family businesses and to present the best succession solutions in the world that increase the likelihood of intergenerational (or non-family) management transfer in small, medium and large family businesses in the 21st century.